2017
DOI: 10.1016/j.cub.2017.09.006
|View full text |Cite
|
Sign up to set email alerts
|

The Cys-Arg/N-End Rule Pathway Is a General Sensor of Abiotic Stress in Flowering Plants

Abstract: SummaryAbiotic stresses impact negatively on plant growth, profoundly affecting yield and quality of crops. Although much is known about plant responses, very little is understood at the molecular level about the initial sensing of environmental stress. In plants, hypoxia (low oxygen, which occurs during flooding) is directly sensed by the Cys-Arg/N-end rule pathway of ubiquitin-mediated proteolysis, through oxygen-dependent degradation of group VII Ethylene Response Factor transcription factors (ERFVIIs) via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
119
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 121 publications
(135 citation statements)
references
References 51 publications
4
119
0
Order By: Relevance
“…without previous S-nitrosylation (White et al, 2017), a role for NO in the degradation of the ERF-VIIs has been observed in vivo. In fact, NO has been shown to promote an N-end rule pathway-dependent proteolysis of full-length ERF-VII factors, as well as artificial ERF-VIIderived Arg-Cys/NERP substrates (MC-GUS, UBI-C-GUS) in Arabidopsis and barley Vicente et al, 2017). However, the mechanism connecting NO to ERF-VII stability still needs to be revealed ; Fig.…”
Section: N-terminal Cys Modificationsmentioning
confidence: 99%
See 4 more Smart Citations
“…without previous S-nitrosylation (White et al, 2017), a role for NO in the degradation of the ERF-VIIs has been observed in vivo. In fact, NO has been shown to promote an N-end rule pathway-dependent proteolysis of full-length ERF-VII factors, as well as artificial ERF-VIIderived Arg-Cys/NERP substrates (MC-GUS, UBI-C-GUS) in Arabidopsis and barley Vicente et al, 2017). However, the mechanism connecting NO to ERF-VII stability still needs to be revealed ; Fig.…”
Section: N-terminal Cys Modificationsmentioning
confidence: 99%
“…This function has been associated with RAP2.2 phosphorylation, following its interaction with an SNRK3 kinase complex that mediates ABA insensitivity. D, ERF-VII stabilization enhances plant tolerance to multiple abiotic stresses (Vicente et al, 2017). During salinity, decreased NO biosynthesis due to NR enzyme impairment has been proposed to lead to ERF-VII protein stabilization in the presence of oxygen.…”
Section: Erf-vii In Plant-pathogen Interactionsmentioning
confidence: 99%
See 3 more Smart Citations